2011
DOI: 10.1007/s12042-011-9078-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of the Brachiaria brizantha Germplasm

Abstract: Brachiaria brizantha (Hochst. ex A. Rich.) Stapf. (syn. Urochloa brizantha (Hochst. ex A. Rich.) R.D.Webster) is a species used primarily as forage in tropical America and Southeast Asia. B. brizantha has been extensively researched since the 1980s with the initiation of the Tropical Forages Breeding Program conducted by the Brazilian Agricultural Research Corporation (Empresa Brasileira de Pesquisa Agropecuária; EMBRAPA), holding one of the largest germplasm collections in the world. This work has identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 27 publications
11
32
1
3
Order By: Relevance
“…The PIC value in this study is within the range reported by Silva et al [14], Jungmann et al [15], and Vigan et al [16], but was lower than that found by Jungmann et al [17] and Pessoa-Filho et al [18]. Similarly, the average numbers of allele detected per loci (5.45) was in the range reported by Silva et al [14], Jungmann et al [15], and Vigan et al [16], but was about half and one-third of that reported by Jungmann et al [17] and Pessoa-Filho et al [18], respectively. However, these comparisons between studies may not be conclusive due to differences in types and number of germplasms and markers used among studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The PIC value in this study is within the range reported by Silva et al [14], Jungmann et al [15], and Vigan et al [16], but was lower than that found by Jungmann et al [17] and Pessoa-Filho et al [18]. Similarly, the average numbers of allele detected per loci (5.45) was in the range reported by Silva et al [14], Jungmann et al [15], and Vigan et al [16], but was about half and one-third of that reported by Jungmann et al [17] and Pessoa-Filho et al [18], respectively. However, these comparisons between studies may not be conclusive due to differences in types and number of germplasms and markers used among studies.…”
Section: Discussionsupporting
confidence: 91%
“…occupy pioneer habitats and generate individuals that are able to exploit new niches or outcompete progenitor species, whereas apomictic polyploid plants can fix heterosis [16,26,30]. 10 This study is an effort to build a collection of Brachiaria ecotypes in Kenya and identify the potential values of these genetic resources in the Brachiaria breeding program.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of death for species in our study seemed to be weed interference; our mechanical control every four months did not effectively eliminate two of the main weed species: the grass B. brizantha in the case of Control site (paddocks), and the leguminous vine P. phaseoloides in the case of Platforms and Cells. These weeds are well adapted to soils that are acidic, clay-like, and with low fertility levels (Vigna et al, 2011) such as those from our sites, and they compete fiercely with trees (Casselman et al, 2006), preventing the natural regeneration of native forest species (Holl et al, 2000). This suggests a need to conduct more frequent mechanical controls on weeds, at least during the first year after planting (Craven et al, 2009).…”
Section: Species Performancementioning
confidence: 98%
“…It is estimated that the total pasture area in Brazil is superior to 200 million ha, with more than its half comprised of cultivated grasses, and the genus Brachiaria occupies about 85% of this area (Vigna et al, 2011).…”
Section: Introductionmentioning
confidence: 99%